The corporate, real estate, household, government and non-bank financial sectors under financial stability - Ramlall, Indranarain (Emerald Publishing Limited, 2018)
Sound financial stability assessments necessitate intensive analysis of different sectors, namely, the household sector, the corporate sector, the real estate sector, the government sector, and the non-bank financial sector. This volume provides a complete analysis and risk assessment of each of these sectors which make up the subtle and intricate fabric which contribute to financial stability. The book considers:micro-prudential and macro-prudential regulations and how they constitute core ingredients to ensure a sound and smooth functioning financial system; the role of household debt as a coveted economic indicator of the building up of financial instability pressures; the relation of the real estate sector to the prevalence of financial crises through asset price bubbles; the role of the corporate sector in financial stability risk analysis. In particular, the balance sheets of the corporate sector are widely examined to uncover feasible risks to financial stability; the role of the government sector, with particular emphasis being laid on public debt management. This book will prove valuable to central bankers, economists, and policy-makers who are involved in the field of financial stability, as well as researchers studying the field.
Keywords: Finance.; Real estate business.; Commercial credit.; Consumer credit.; Business & Economics -- Finance -- General.; elektronické knihy; electronic books